A modal decomposition approach for experimental buckling analysis of thin-walled lipped channel columns. (1st April 2022) - de Salles, Guilherme C.; Batista, Eduardo de M.; Cardoso, Daniel C.T.
Highlights: A modal decomposition method to numerical and experimental results of lipped channel columns with fixed-ends is developed. The method adopts shape functions for the main buckling modes: local, distortional and global (minor axis flexure) modes. The method is validated against generalized beam theory (GBT) for columns undergoing L-D interaction . The application of the method to experimental results provides a clear identification of the interaction phenomenon. Abstract: This paper presents a method to perform the decomposition of a lipped channel column's general deformed shape into the three main buckling modes: local, distortional and flexural global modes. Simple shape functions for each buckling mode are assumed and through an error minimization process the participation of each mode in the deformed shape of the column can be assessed. In a first step, the method is validated against numerical results using generalized beam theory (GBT) modal decomposition for columns undergoing L-D interaction. It is shown that the proposed technique provides good estimates for each buckling modes that contributes to the deformed shape. Lastly, an experimental column previously tested by the authors is analyzed using the proposed modal decomposition method. Although simpler than GBT and the constrained finite strip method (cFSM), the obtained results show that the proposed method can be a valuable and simple tool for a quick assessment of columns' behavior, especially experimental specimens.